Project-based Learning Implementation to Cultivate Preservice English Teachers’ 21st Century Skills - Evi Puspitasari (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2020)
The contribution of Project-based Learning (PbL) to 21st century learning skill development has been widely discussed by experts. This present qualitative research aims at exploring how PbL is applied in Lantern School of English Education (LSEE), an undergraduate program in Indonesia that produces an English teacher. In further, this research also looked at how the implementation enhanced the students’ 21st century learning skills comprising creativity, critical thinking, collaboration, and communication. Considering those objectives, this research stood under qualitative approach and specifically employed case study design in order to investigate a single case which was project-based learning implementation in a particular context. The data were collected from interview, observation, and relevant documents which in this case, reflective essay, syllabus and students’ final projects. Observation and syllabus were used to investigate the implementation of PbL in LSEE, interviews and was to gather information about how the implementation cultivated students 21st century skills, while students’ works and reflective essay were to triangulate information from the other data collection techniques. After gaining the data, all were analysed using coding process to obtain the embedded themes as findings. The findings showed that the institution implemented PbL through the assessment, classroom activities, teacher roles, and student roles. Based on the students’ viewpoints, project-based assessment, group classroom activities, teachers being a facilitator, and students’ centeredness were successfully trained their ability on creativity, critical thinking, collaboration, and communication. Conclusion and recommendation are also presented after the findings were discussed.